Analiza ravni flikerja v prenosnem omrežju Slovenije - Blažič, Boštjan (Elektrotehniški vestnik, 2006)
With deregulation of the Slovenian electricity market power quality has becomean important issue for the transmission system operator (TSO), since poor power quality is no longer tolerated by electricity consumers. One of thegreatest disturbances affecting power quality in the Slovenian transmissionnetwork is voltage f1icker. It is mostly caused by arc fumaces producing voltage amplitude fluctuations resulting trom strongly f1uctuating power consumption.Voltage variations at frequencies between 0.5 and 25 Hz are of a special concem. They give rise to flicker, reflecting itself in changes in luminosity of lamps. As these disturbances may travel over a large area of the transmission network, they affect a considerable number of unsatisfied andconsequently complaining consumers connected to distribution networks. A common equivalent circuit of arc fumace connection to the high-voltage (HV) network is shown in Fig. 1. The f1icker level at the point of arc fumace connectionto the transmission network is determined by the arc fumace operation and network impedances (Eq. 1). In large and complex networks, spreading of f1icker distortion is inf1uenced by many factors making analytical formulation difficult. Such networks can be analysedby means of simulation where special attentionis paid to correct representation of networktopology, generators and f1ickersources. Various power quality I measurements have already been made in the Slovenian HV transmission network (measurement points are listed in Table 1) in parallel with some permanent measurements made by the Slovenian TSO (ELES) 2-7. The measurement resultsconfirm that the main sources of f1ickerare large arc-fumaces in iron works Ravne, Štore and Jesenice. The measurement results for the selected points are presented in Table 2.and geographical areas with f1icker with the value above I are shown in Fig. 2. Simulation models of the Slovenian transmission network were implemented in SINCAL and PSCAD. Besides the basic network elements (generators, transformers, transmission lines and linear loads), an arc fumace model 8-11 and IEC-based f1icker-meter model 12, 13 were also developed. The arc-fumace model operation is described with equations (2)-(5). The complete network model and the arc fumaces models were calibrated to ref1ectas much as possible of the real network conditions and measurement results. With simulations in SINCAL, the flicker levels for the whole HV network were determined. On the other hand, the PSCAD model provides the basis for the analysis and evaluation of different flicker mitigation solutions. Flicker levels obtained with the two simulation tools are given in Table 2 allowing for a comparison with the measurement results. Table 3 shows the share of nodes in the HV network based on the flicker value. It is evident that flicker exceeds the value of 1 in 39% of all the nodes in 110 kV level.
Keywords: fliker; električno omrežje; električna napetost; Slovenia; Slovenija